EVALUASI BEASISWA BIDIKMISI PADA MAHASISWA DI UNIVERSITAS PAPUA - Usman, Sarah; Suruan, Ted (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2025)
Bidikmisi is a scholarship program which held by the government in order to give contributions for freshmen in the university level with academic potencies and those who come from underprivileged economic background. This research was conducted on the students which are the receivers of Bidikmisi Scholarship batch 2016-2019. The purpose of this research is to undertand the socioeconomic status of the families, the acceptance system, and the usage of the scholarship by the receivers of Bidikmisi Scholarship Program.This research is a quantitative-descriptive research with 3.915 receivers of the scholarship as the population. The research method which used is the proportional stratified random sampling. It involved 98 respondents from 11 faculties as the samples in the statistical-descriptive analysis.The result of this research, in term of socioeconomic status, shows that the average income of the families of Bidikmisi Scolarship receivers is in the amount of Rp 2.050.000 -Rp 4.000.000. Due to the acceptance system of the scholarship, the fund from Bidikmisi is normally accepted by the receivers in the middle of the semester. The highest usage of the scholarship is in the additional needs which reach the number of Rp 1.384.007. It is compared to the academic needs which is Rp 364.213, and personal needs which is around Rp 215.899. Based on these results the university is hoped to put more attention on the students with underprivileged economic background and also consider to put the acceptance date of the scholarship at the beginning of the semester to maximize the utilization of the scolarship based on the purpose of Bidikmisi.